2011
DOI: 10.5539/elt.v4n2p151
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Metacognitive Reading Strategies Used by Native Speakers of Arabic When Reading in English and Arabic

Abstract: This study examined the metacognitive awareness and reading comprehension strategies used by advanced proficiency ESL readers whose native language is Arabic. The study looked at the perceived use of reading strategies by Arabic native speakers in Arabic and English and their actual use of these strategies in reading academic texts in the two languages. The goal was to compare the reading strategy profiles of Arabic native speakers in English and Arabic through quantitative means using a self-report survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 23 publications
7
46
1
3
Order By: Relevance
“…Participants' preference for 'problem-solving' reading strategies similarly in L1 and L2/FL followed by global and support strategies was also indicated in previous studies (Poole 2010;Alsheikh & Mokhtari 2011;Yüksel & Yüksel 2012). Problem-solving strategies are most preferable because they are the kind of 'top-down' strategies that contribute to a more effective reading comprehension.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 75%
See 1 more Smart Citation
“…Participants' preference for 'problem-solving' reading strategies similarly in L1 and L2/FL followed by global and support strategies was also indicated in previous studies (Poole 2010;Alsheikh & Mokhtari 2011;Yüksel & Yüksel 2012). Problem-solving strategies are most preferable because they are the kind of 'top-down' strategies that contribute to a more effective reading comprehension.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 75%
“…In relation to similar studies conducted with adults, no consensus was indicated among the researchers regarding the comparison of frequency of L1 and L2 reading strategies use. Thus, it has been found that the frequency of reading strategies use was higher in L2 than in L1 (Kong 2006;Alsheikh & Mokhtari 2011); however in some other studies the opposite results were revealed (Tsai, Ernst & Talley 2010;Maarof & Yaacob 2011) or no significant difference between L1 and L2/FL reading strategies was indicated (Anderson 1991).…”
Section: The Current Studymentioning
confidence: 95%
“…Studies that do not support these findings do also exist. Alsheikh andMokhtari's (2011) andTavakoli's (2014) participants favored the support reading strategies most. Akkarararitwutthikun and Sappan (2013) and Hoang (2016) and Kocaman and Beskadesler (2016), revealed that their participants were relying on global reading strategies most.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies simply investigated the learners' awareness of these strategies (Marteniz, 2008;Singhal, 2001;Akkararitutthikun & Sappappan, 2013;Lien, 2014;Shikano, 2013) while a good number tried to investigate the existence of any relations between the employment of these strategies and other variables. For example, Jom'a (2013), Alsheikh and Mokhtari (2011), Mirzapour and Mozaheb (2015) and Hoang (2016) explored the relation between using the reading strategies and the learners' proficiency level.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit, their agreement of the superiority of the monolinguals, there are some differences in viewing their language learning. From the Arab bilinguals' perspectives learning another language could be a subtractive process, they indicated linguistic complexity between Arabic and English, they pointed to linguistic differences, they also indicated some selected strategies that could be transfer to English and they actually translate from English to Arabic (see Alsheikh, 2014;Alsheikh & Mokhtari, 2011;Alsheikh, 2009)). On the other hand, the three African multilinguals see their multilingualism as an asset of an additive bilingualism, linguistic clarity due to their exposure to different linguistic systems; they indicated that there are some linguistic similarities between romance languages such as French and English language; they also pointed there are some differences among English, French and Hausa; they also pointed to more strategies transfer than the bilinguals which corroborated findings from Alsheikh (2011).…”
Section: Discussionmentioning
confidence: 99%